2010
DOI: 10.2202/1542-6580.2260
|View full text |Cite
|
Sign up to set email alerts
|

Control of Reactive Distillation Column: A Review

Abstract: The objective of this paper is to give a critical survey of the present status within the field of control of a reactive distillation column. Control of a reactive distillation column is a challenging task due to process nonlinearity and complex interactions between the vapor-liquid equilibrium and chemical reactions. There are different types of control methodologies, which have been studied in the reactive distillation, ranging from a simple proportional-integral (PI) controller to advanced model predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 65 publications
(100 reference statements)
0
23
0
Order By: Relevance
“…The reactive distillation technology for MTBE production has been studied [37][38][39] and advantages of reactive distillation has been well established in the case of MTBE.…”
Section: Case Study: Mtbe Synthesismentioning
confidence: 99%
“…The reactive distillation technology for MTBE production has been studied [37][38][39] and advantages of reactive distillation has been well established in the case of MTBE.…”
Section: Case Study: Mtbe Synthesismentioning
confidence: 99%
“…The efficient implementations of MPC and dynamic optimization in industrial cases were already reported for several non-linear chemical processes including hybrid systems, such as reactive separations and in particular reactive distillation (Agachi et al 2006;Nagy et al 2007;Sharma and Singh 2010;Kiss 2010;Rewagad and Kiss 2012).…”
Section: Dynamics and Control Of Reactive Distillationmentioning
confidence: 99%
“…The domain of the two different characteristic can be seen on the Figure 16. On border of the two parts hysteresis phenomenon is detected [7].…”
Section: The Middle Level Temperature Controlmentioning
confidence: 99%